2021
DOI: 10.1002/jms.4563
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of imaging mass spectrometry in drug discovery and development: Making a difference by driving decision making

Abstract: In this special feature article, Steve Castellino and co‐authors highlight why matrix‐assisted laser desorption/ionization imaging mass spectrometry (MALDI IMS) technology is an important innovation, which can improve and enhance drug discovery and development. Currently, most IMS studies conducted in drug discovery and development focus on the quantitative distribution of drug candidates and their metabolites in animal model tissues. The need to understand the biodistribution of drugs in tissues is not a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…15,50,51 MALDI and DESI microprobe imaging are performed in a similar manner to SIMS, except that the incident primary ion beam has been replaced with a sampling beam of photons (i.e., a laser in MALDI) or a stream of charged droplets (i.e., ESI droplets in DESI). MALDI is currently the most widely used iteration of imaging mass spectrometry and has been used recently to image metabolic perturbations indicative of host-microbiome interactions (Figure 2), 52-64 track neurotransmitters during neurodegenerative disease progression, [65][66][67][68][69][70][71] map N-glycosylation changes in cancer, [72][73][74][75][76][77] monitor pharmaceutical distributions in target organs, [78][79][80][81][82][83][84] and use peptide profiles for clinical disease classification. [85][86][87][88] Similarly, DESI has been used to measure metabolite profiles for disease classification and cancer diagnosis (Figure 3), [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] map lipid profiles for tumor margin analysis during resection,…”
Section: Generating Ions From Surfacesmentioning
confidence: 99%
“…15,50,51 MALDI and DESI microprobe imaging are performed in a similar manner to SIMS, except that the incident primary ion beam has been replaced with a sampling beam of photons (i.e., a laser in MALDI) or a stream of charged droplets (i.e., ESI droplets in DESI). MALDI is currently the most widely used iteration of imaging mass spectrometry and has been used recently to image metabolic perturbations indicative of host-microbiome interactions (Figure 2), 52-64 track neurotransmitters during neurodegenerative disease progression, [65][66][67][68][69][70][71] map N-glycosylation changes in cancer, [72][73][74][75][76][77] monitor pharmaceutical distributions in target organs, [78][79][80][81][82][83][84] and use peptide profiles for clinical disease classification. [85][86][87][88] Similarly, DESI has been used to measure metabolite profiles for disease classification and cancer diagnosis (Figure 3), [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] map lipid profiles for tumor margin analysis during resection,…”
Section: Generating Ions From Surfacesmentioning
confidence: 99%
“…Over the past decades, pharmaceutical companies, instrument manufacturers and academic institutions have been actively involved in researching and applying MSI in drug discovery and development. [1][2][3][4][5] Highlighted below are a few key research areas that have been reported to drive MSI application in pharmaceutical research:…”
Section: Perspectivementioning
confidence: 99%
“…The nature of MSI enables the identification of drug molecules and facilitates researchers in studying their localization at the molecular level. Over the past decades, pharmaceutical companies, instrument manufacturers and academic institutions have been actively involved in researching and applying MSI in drug discovery and development 1–5 . Highlighted below are a few key research areas that have been reported to drive MSI application in pharmaceutical research: Advancing of MSI techniques: Pharmaceutical MSI researchers have been focusing on refining existing MSI techniques, such as matrix‐assisted laser desorption/ionization (MALDI), secondary ion mass spectrometry (SIMS) 2 and DropletProbe Mass Spectrometry (DPMS) 6 .…”
Section: Perspectivementioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization (MALDI) imaging mass spectrometry (IMS) has emerged as a powerful analytical technology in the pharmaceutical industry given its unique ability to generate quantitative molecular images of an unlabeled drug and endogenous molecular species in tissues and cells with high sensitivity and speci city. [25,26] To further understand and identify the anatomical distribution of drug release, we utilized MALDI IMS to examine the quantitative distribution of GSK2485680 and the liposome components in infected and non-infected hindlimb tissues.…”
Section: Introductionmentioning
confidence: 99%